THE TRAINING OF SOCIAL COMPETENCE IN AGGRESSIVE PREADOLESCENTS - SAVCA Lucia; NANDOR Nemes Madoxa (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Puberty is a period of crisis, which consists of rapid radical bio-psycho-social transformations, which can negatively influence pubertal behavior. In adverse conditions, characterized by high levels of domestic conflict, a reduced level of communication, emotional aggression or neglect have a negative impact on the minor's relationship with others. In the given study, we reflected the content of the training program for social competence (CS), created by us, which included the CASEL model, but also effective techniques from different therapies. 28 preadolescents participated in the formative group: 14 students in GE and 14 students in GC. 13 sessions lasting 90 min were held once a week. Retest analysis with the Wilcoxon rank test was performed with a Bonferroni correction applied, resulting in an observed significance level of p<0.05 for all comparisons at the level of the social skills variable, and a Bonferroni correction applied, resulting in an observed significance level of p<0.05 for all comparisons at the level of the total aggression variable for GE students.